Mental-Based Summative Assessment: Reconstructing Character Evaluation At Pondok Modern Darussalam Gontor Putri - Abdul Hamid; Aca Syahtybie; Mohamad Rifki Ilham; Nurlaela; Lailiya Rachmawati; Nurjannah; Fahmi Fahlevi (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
Character and mental education remain difficult to assess through conventional summative evaluation because most school assessment systems prioritise cognitive achievement and written tests. This problem becomes more critical in Islamic boarding schools, where students’ character is shaped through continuous religious, social, organisational, and dormitory life. This study aims to analyse how Pondok Modern Darussalam Gontor Putri reconstructs summative assessment to evaluate students’ mental and character development through the Mental Personality instrument. This study employed a descriptive qualitative case study using participatory observation, document analysis of the Mental Report Card, and relevant literature on mental education, character education, and authentic assessment. The findings show that mental-based summative assessment at Gontor Putri is operationalised through 16 observable indicators covering spiritual, social, personal resilience, and gender-responsive domains. Assessment is conducted through public speaking, scouting, organisational duties, worship discipline, and 24-hour dormitory life, then validated through collective deliberation among educators and supervisors. This study implies that character assessment can become more systematic and accountable when abstract values are translated into behavioural indicators and assessed through authentic, continuous observation.